Progress towards an improved Precambrian seawater 87Sr/86Sr curve - Chen, Xi; Zhou, Ying; Shields, Graham A. (Earth-science reviews, 2022)
The secular trend of seawater strontium isotope ratio (87Sr/86Sr) reflects changes in the relative contributions of continental versus mantle reservoirs to ocean composition, and informs global tectonic events, weathering rates and biogeochemical cycling through Earth history. However, the Precambrian seawater 87Sr/86Sr curve is known in far less detail than its Phanerozoic counterpart. For this study, we compiled 2249 strontium isotope ratios of Precambrian marine sedimentary rocks published since 2002, alongside previously compiled older data. Here we evaluate the uncertainty of all published data for constraining coeval seawater 87Sr/86Sr using four criteria (depositional environment, diagenetic alteration, age constraint and dissolution method). The resultant seawater 87Sr/86Sr curve uses mainly ‘high certainty’ data and shows an overall increasing trend from ~0.7005 at c. 3.5 Ga to ≥0.7089 towards the end of the Ediacaran Period. The improved curve shows an earlier deviation of seawater 87Sr/86Sr from the contemporaneous mantle by c. 3.5 Ga, which might reflect the first significant emergence of evolved continental crust related to nascent tectonics. Additionally, the updated curve records two major rises at 2.5-2.2 Ga and 1.9-1.7 Ga in addition to a well-established event at 0.8-0.5 Ga. Despite the relative scarcity of high-certainty data, these two increases are consistent with enhanced continental weathering following the onset of oxidative weathering and assembly of the supercontinent Nuna, respectively. Although confirmation of these two events awaits more high-certainty data, Precambrian seawater 87Sr/86Sr experienced stronger oscillations and better correspondence with supercontinent cycles than previously shown.